Security Issues and Comparative Analysis of Security Protocols in Wireless Sensor Networks: A Review - Nuristani, AK; Thakur, Jawahar (International Journal of Computer Sciences and Engineering, 2025)
Wireless sensor network (WSN) is a wireless network with large number of sensor nodes or it could be defined as a set of distributed devices which could be used to monitor sensible and natural conditions. These sensors can execute processing and sensing tasks, and additionally equipped for communicating with each other. Because of the extensive area of its applications it became one of the premier research topics recently. The main objective of wireless sensor network is regularly to gather sensing data from all sensors to particular sink nodes (base stations) and after that performing additionally operations at these sink nodes. Currently wireless sensor networks are available as a subject at advanced undergrad and graduate levels at some universities around the world. One of the challenges in WSNs is to devise and implement high security protocols with limited resources. This paper debated the security issues; challenges and protocols that are discussed and reviewed on the basis of attributes (confidentiality, availability, freshness, encryption methods, MAC authentication, key management, attacks protected and scalability) and tabulated WSNs security protocols, on the basis of (authors, protocols, advantages, disadvantages and applications) based on researches done by the researchers.